Investigation of the Relationship between Vertical Stiffness and Time to Stability Index during Landing - Mohammadamin Mohammadian; Heydar Sadeghi; Mehdi khaleghi-Tazji (مجله پژوهش در علوم توانبخشی, 2020)
Introduction: Theoretically, stiffness is effective in the stability and can subsequently reduce the risk of injury. The aim of this study was to investigate the relationship between vertical stiffness and time to reach stability during landing.Materials and Methods: Twenty healthy active men participated voluntarily in this study. Vertical hopping tests were performed bilaterally, unilaterally on dominant leg, and unilaterally on non-dominant leg with self-selected, controlled (frequency: 2.2 Hz), and maximal strategies during which vertical stiffness variables were determined. Single-leg landing test from platform was performed to determine the variables of time to reach stability in vertical, anterior-posterior (AP), and medio-lateral (ML) directions on the force plate. The relationship between vertical stiffness and time to reach stability variables was determined by Pearson correlation test (P ≤ 0.05).Results: A significant positive relationship was observed between maximum unilateral vertical stiffness on dominant leg (r = 0.45, P = 0.048) and non-dominant leg (r = 0.52, P = 0.012) with time to reach stability in AP direction.Conclusion: These findings suggest that high level of vertical stiffness increases the AP time to reach stability and consequently increases the risk of associated injuries.